PENGARUH FAKTOR KARAKTERISTIK PEKERJAAN DAN IKLIM ORGANISASI TERHADAP PRODUKTIVITAS PEKERJA (Suatu Kajian Pada Operator Bagian Produksi di Perusahaan Manufakturing Metal Stamping di Kota Tangerang - Banten) - Hermanto Hermanto (Faktor Exacta, 2010)
This research starting from suspect that worker productivity ( Y) determined by two principal variables that is performance and motivation of work of the workers. Variable - variable determining motivation of work for example work characteristic (x¹) and organization climate (x²).produktivity as comparison between outputs with input in set of certain in working every worker. This research general purpose is to obtain information based on empirical data about magnitude and direction of organizational work characteristic influence and climate to worker productivity. This research haves the character of " ex post facto", with subject sebayak 100 operator worker part of produce of PTHTP Metalworks in Tangerang-banten. This research data obtained with observation guidance of productivity, questionaire job diacnostic survey, and questionaire Iklim organization. Processing and data analysis applies program computer SEM Lisrel.8.72 student. Result of this research menunjukan : There is influence joinly organizational work characteristic and climate to productivity pekerjaTerdapat positive connection between 4 ( four) work characteristic elements ( skilled variation, task identity, signifikansi task, autonomy) with work characteristic, except element of feedback doesn't correlate positifTerdapat the relation of which are positive and haves a meaning (of) between organizational climates and worker productivity. To 3 ( three) of each element correlated positively with worker productivity. Except element of orientation of reward and orientation of development and kemajuanHasil this research brings implication, for example organizational climate variable in PTHTP Metalworks need to be controlled to maintain and or increases worker productivity. Keywords: Worker Productivity, Job Characteristic, Organizational Climate.